Comparing the efficacy of hyaluronic acid products with various molecular weights as mono and combined with chondroitin sulfate regimens in treatment of patients with stage I–III knee osteoarthritis - V. E. Bialik; M. A. Makarov; E. I. Bialik; S. A. Makarov; V. A. Nesterenko; M. R. Nurmukhametov (Научно-практическая ревматология)
Aim: to evaluate the effectiveness of hyaluronic acid (HA) preparations with different molecular weights and in combination with chondroitin sulfate (HS) for intra-articular (IA) injections in the treatment of patients with stage I–III knee OA.Subjects and methods. IA HA injections were performed 160 patients with primary and post-traumatic knee OA of the I–III stages at the department of traumatology-orthopedics, V.A. Nasonova Research Institute of Rheumatology for the period from September 2017 to June 2019. Patients were divided into 4 groups. Group 1 consisted of 80 patients treated with low molecular weight (LMW) HA, group 2–20 patients treated with medium molecular weight (MMW) HA, group 3–30 patients treated with high molecular weight (HMW) HA, and group 4–30 patients who were intraarticular introduced HA with HS. The course of IA injections was 2 for LMW, HMW, and HA with HS, and 3 for MMW HA. Injections were performed with an interval of 1 week. To evaluate the results of treatment, we studied the intensity of pain according to VAS and the total score of KOOS before treatment and on follow-up examinations 1, 3 and 6 months after the course of IA HA injections.Results. The maximum reduction in pain with IA HA injections at stage I of knee OA occurred by 3 months after the course of treatment. Moreover, improvement was detected by 1 month in 84.3% of cases, and remained until the end of the study in 71.1% of patients. All HA preparations used in stage I of knee OA were effective. At stage II of the knee OA after 3 months after the course of IA HA, different efficiencies of HA preparations were revealed. So, in the groups of LMW, MMW and HA with HS, the improvement persisted up to 3 months, and in the group of HMW HA – up to 1 month. After 3 months, the best results were shown by HA with HS, by 6 months the results were comparable. IA HA injections at the II stage of knee OA led to good and excellent results 1 month after the course of treatment in 53.9% of cases, but by the end of the study, improvement remained in only 30.8% of patients. In the case of the use of HA in stage III of the knee OA, the effectiveness of the studied drugs was comparable, and the maximum improvement was achieved by 1 month. The positive effect of IA HA injections in patients with stage III of the knee OA one month after the course of treatment was obtained in 40.6% of cases, by 3 months it decreased to 18.8%, and by 6 months – to 15.7% of patients.Conclusions. IA injections of HA at stage I of the knee OA is a highly effective method of conservative treatment, which allows to relieve pain and improve the condition of the knee joint for a period of 6 months or more. The use of HA preparations at stage II of the knee OA allows reducing pain up to 3 months with IA injections of LMW and MMW HA, as well as HA with HS. HMW HA helps reduce pain intensity for a period of 1 month. The use of HA preparations in stage III of the knee OA leads to a short-term relief of symptoms of OA.